2010
DOI: 10.1097/qad.0b013e328339fe53
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate, chronic kidney disease and antiretroviral drug use in HIV-positive patients

Abstract: In this nonrandomized large cohort, increasing exposure to tenofovir was associated with a higher incidence of CKD, as was true for indinavir and atazanavir, whereas the results for lopinavir/r were less clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
350
13
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(397 citation statements)
references
References 59 publications
20
350
13
14
Order By: Relevance
“…A previous study suggested an association between the use of ATV, TDF, or indinavir and creatinine clearance, as indicated by a persistent reduction in glomerular filtration rate over time. 56 The biological explanations for these findings are unclear, but may include glomerular dysfunction, high renal excretion rates, and/or crystalluria. 56 Though the current study observed modest changes over 48 weeks, the ARTEMIS study did not show any changes in creatinine clearance over 96 weeks, 39 suggesting that longterm use of DRV/r has little effect on creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested an association between the use of ATV, TDF, or indinavir and creatinine clearance, as indicated by a persistent reduction in glomerular filtration rate over time. 56 The biological explanations for these findings are unclear, but may include glomerular dysfunction, high renal excretion rates, and/or crystalluria. 56 Though the current study observed modest changes over 48 weeks, the ARTEMIS study did not show any changes in creatinine clearance over 96 weeks, 39 suggesting that longterm use of DRV/r has little effect on creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Results from European cohorts show a prevalence of kidney disease (eGFR < 60 mL/ min/1.73 m 2 ) to be 2-5%. [21][22][23] The relatively low median age (48 years) of our patients likely explains this finding. However, the high prevalence of patients with signs of renal damage, most of whom had an eGFR > 60 mL/min/1.73 m 2 is similar to other results recently reported elsewhere, 21 and, contrary, is lower than others regarding the proportion of proteinuria detected.…”
Section: Discussionmentioning
confidence: 45%
“…30,31 Our data showed that the use of tenofovir combined with a protease inhibitor increased the risk of kidney disease (abnormal eGFR and abnormal UPC or UAC ratios), as previously described in large cohorts. 15,22,32 Higher tenofovir plasma concentration was associated with alterations in renal markers (both glomerular and tubular), 33,34 and the highest plasma exposure was associated with the concomitant use of protease inhibitors. 35 However, whether co-administered or not with protease inhibitors, tenofovir was not associated with proteinuria > 300 mg/g in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although this difference was not significant, the results are not unexpected due to the negative impact of protease inhibitors on tenofovir-related kidney or bone toxicity. 23,24 The small sample size of the abacavir-lamivudine group is a limitation of the study. However, the only existing data on the combination abacavir/lamivudine plus raltegravir included 35 antiretroviral-naive patients, and thus the number of patients with this combination of interest was almost double in our study.…”
Section: Discussionmentioning
confidence: 99%